A method for predicting the water-flowing fractured zone height based on an improved key stratum theory - He, Jianghui; Li, Wenping; Fan, Kaifang; Qiao, Wei; Wang, Qiqing; Li, Liangning (International journal of mining science and technology, 2023)
In the process of using the original key stratum theory to predict the height of a water-flowing fractured zone (WFZ), the influence of rock strata outside the calculation range on the rock strata within the calculation range as well as the fact that the shape of the overburden deformation area will change with the excavation length are ignored. In this paper, an improved key stratum theory (IKS theory) was proposed by fixing these two shortcomings. Then, a WFZ height prediction method based on IKS theory was established and applied. First, the range of overburden involved in the analysis was determined according to the tensile stress distribution range above the goaf. Second, the key stratum in the overburden involved in the analysis was identified through IKS theory. Finally, the tendency of the WFZ to develop upward was determined by judging whether or not the identified key stratum will break. The proposed method was applied and verified in a mining case study, and the reasons for the differences in the development patterns between the WFZs in coalfields in Northwest and East China were also fully explained by this method.